Osteoblastic response to biomaterials surfaces: Extracellular matrix proteomic analysis - Graeff, Marcia Sirlene Zardin; Tokuhara, Cintia Kazuko; Sanches, Mariana Liessa Rovis; Buzalaf, Marília Afonso Rabelo; Rocha, Luis Augusto [UNESP]; de Oliveira, Rodrigo Cardoso (Wiley, 2022)
The cellular response to surfaces is mediated, among other factors, by the extracellular matrix (ECM). However, little is known about the ECM proteome during mineralization. Our objective was to compare the ECM composition formed by osteoblast on different materials surfaces with proteomic analysis. Three types of biomaterial surfaces (pure titanium, anodized titanium, and zirconia) were used. Osteoblasts (MC3T3 linage) cells were cultivated on the biomaterials for 7, 14, and 21 days with the osteogenic medium. For the proteomic analysis, the specimens were washed, decellularized, and the ECM was collected. The majority of the typical ECM proteins, out of a total of 24 proteins identified, was expressed and regulated equally on the three biomaterials tested. Alpha-1,4 glucan phosphorylase was found to be down-regulated on zirconia on the seventh day, while at the same time, glycogen phosphorylase brain form was up-regulated on anodized titanium, both when compared with pure titanium (ratio: 1.06 and 0.97, respectively). And after 14 days of culture, glycogen phosphorylase brain form was downregulated on zirconia when compared with pure titanium (ratio: 0.90), suggesting the influence of material surface roughness and chemical composition on energy metabolism. Proteins related to bone development like Transforming growth factor beta-3 and Fibroblast growth factor 8 were found exclusively on pure titanium on the 21st day. Altogether, our results show a possible influence of material surfaces on the composition of ECM.
Keywords: biomaterials; extracellular matrix; osteoblasts; proteomics